Paropsis charybdis defoliation of Eucalyptus stands in New Zealands central North Island - Murphy, B.D.; Kay, M.K. (New Zealand Plant Protection, 2000)
Paropsis charybdis the most serious pest of Eucalyptus in New Zealand was controlled with the introduced Australian egg parasitoid Enoggera nassaui in the late 1980s Using frass traps to monitor P charybdis populations we report that pest outbreaks still occur resulting in heavy defoliation of susceptible Eucalyptus species The results suggest that the presence of large larval populations and commensurate defoliation result from poor spring parasitism by the parasitoid A second wave of P charybdis oviposition is effectively attacked preventing late season defoliation by larvae A climatic mismatch of E nassaui is suspected to be the cause of this poor performance